Predictive factors of outcome following staphylococcal peritonitis in continuous ambulatory peritoneal dialysis - de Lourdes Ribeiro de Souza da Cunha, M. [UNESP]; Montelli, A. C. [UNESP]; Fioravante, A. M. [UNESP]; Batalha, J.E. Neves [UNESP]; Caramori, J.C. Teixeira [UNESP]; Barretti, P. [UNESP] (Dustri-Verlag Dr. Karl Feistle, 2005)
Background and aims: Staphylococcus epidermidis and other coagulase-negative staphylococci (CoNS) are the most common agents of continuous ambulatory peritoneal dialysis (CAPD) peritonitis. Episodes caused by Staphylococcus aureus evolve with a high method failure rate while CoNS peritonitis is generally benign. The purpose of this study was to compare episodes of peritonitis caused by CoNS species and S. aureus to evaluate the microbiological and host factors that affect outcome. Material and methods: Microbiological and clinical data were retrospectively studied from 86 new episodes of peritonitis caused by staphylococci species between January 1996 and December 2000 in a university dialysis center. The influence of microbiological and host factors (age, sex, diabetes, use of vancomycin, exchange system and treatment time on CAPD) was analyzed by logistic regression model. The clinical outcome was classified into two results (resolution and non-resolution). Results: The odds of peritonitis resolution were not influenced by host factors. Oxacillin susceptibility was present in 30 of 35 S. aureus lineages and 22 of 51 CoNS (p = 0.001). There were 32 of 52 (61.5%) episodes caused by oxacillin-susceptible and 20 of 34 (58.8%) by oxacillin-resistant lineages resolved (p = 0.9713). Of the 35 cases caused by S. aureus, 17 (48.6%) resolved and among 51 CoNS episodes 40 (78.4%) resolved. Resolution odds were 7.1 times higher for S. epidermidis than S. aureus (p = 0.0278), while other CoNS had 7.6 times higher odds resolution than S. epidermidis cases (p = 0.052). Episodes caused by S. haemolyticus had similar resolution odds to S. epidermidis (p = 0.859). Conclusions: S. aureus etiology is an independent factor associated with peritonitis non-resolution in CAPD, while S. epidermidis and S. haemolyticus have a lower resolution rate than other CoNS. Possibly the aggressive nature of these agents, particularly S. aureus, can be explained by their recognized pathogenic factors, more than antibiotic resistance. ©2005 Dustri-Verlag Dr. K. Feistle.
Keywords: CAPD; Oxacillin resistance; Peritonitis; Predictive factors; Staphylococci